The Health Department of Sicily â€œRegional recommendations for hospital discharge and communication with patients after admission due to a cardiologic eventâ€ Decree - Abrignani, Maurizio Giuseppe; De Luca, Giovanni; Gabriele, Michele; Tourkmani, Nidal (Monaldi Archives for Chest Disease, 2015)
Mortality and rehospitalizations still remain high after discharge for an acute cardiologic event. In this context, hospital discharge represents a potential pitfall for heart disease patients. In the setting of care transitions, the discharge letter is the main instrument of communication between hospital and primary care. Communication, besides, is an integral part of high-quality, patient-centered interventions aimed at improving the discharge process. Inadequate information at discharge significantly affects the quality of treatment compliance and the adoption of lifestyle modifications for an effective secondary prevention. The Health Department of Sicily, in 2013, established a task force with the aim to elaborate â€œRegional recommendations for hospital discharge and communication with patients after admission due to a cardiologic eventâ€, inviting to participate GICR-IACPR and many other scientific societies of cardiology and primary care, as discharge letter and communication are fundamental junctions of care transitions in cardiology. These recommendations have been published as a specific decree and contain: â€“ a structured model of discharge letter, which includes all of the parameters characterizing patients at high clinical risk, high thrombotic risk and low risk according to the Consensus document ANMCO/GICR-IACPR/GISE; is thus possible to identify these patients, choosing consequently the most appropriate follow-up pathways. A particular attention has been given to the â€œMedication Reconciliationâ€ and to the identification of therapeutic targets; â€“ an educational Kit, with different forms on cardiac diseases, risk factors, drugs and lifestyle; â€“ a check-list about information given to the patient and caregivers. The â€œRecommendationsâ€ represent, in conclusion, the practical realization of the fruitful cooperation between scientific societies and political-administrative institutions that has been realized in Sicily in the last years.